2018
DOI: 10.1152/ajprenal.00106.2018
|View full text |Cite
|
Sign up to set email alerts
|

NKA enhances bladder-afferent mechanosensitivity via urothelial and detrusor activation

Abstract: Tachykinins are expressed within bladder-innervating sensory afferents and have been shown to generate detrusor contraction and trigger micturition. The release of tachykinins from these sensory afferents may also activate tachykinin receptors on the urothelium or sensory afferents directly. Here, we investigated the direct and indirect influence of tachykinins on mechanosensation by recording sensory signaling from the bladder during distension, urothelial transmitter release ex vivo, and direct responses to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 51 publications
(61 reference statements)
2
38
0
Order By: Relevance
“…; Grundy et al . ). Such assumptions, however, overlook possible differential regulation of release and/or metabolism of mediators at the apical and basolateral sides of urothelium that other studies have suggested (Yu et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Grundy et al . ). Such assumptions, however, overlook possible differential regulation of release and/or metabolism of mediators at the apical and basolateral sides of urothelium that other studies have suggested (Yu et al .…”
Section: Discussionmentioning
confidence: 97%
“…Such concerns apply to both the use of the entire bladder wall and of isolated bladder mucosa as flat sheets. Some studies have measured release of mediators into the bladder lumen during filling and assumed that luminal release of mediators reflects the profile of mediators in subU/LP where afferent nerves and other cells with receptors for urothelial mediators might reside (Daly et al 2014;Beckel et al 2015;Gonzalez et al 2016;Grundy et al 2018). Such assumptions, however, overlook possible differential regulation of release and/or metabolism of mediators at the apical and basolateral sides of urothelium that other studies have suggested (Yu et al 2006;Yu, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst we did not investigate the precise mechanism driving bladder afferent sensitivity in this study, it is likely that as urothelial permeability is increased, urinary contents gain access to afferent nerves to either cause afferent hypersensitivity directly, or indirectly via actions on urothelial cells. We and others have shown that a variety of endogenous mediators can activate bladder afferents, causing afferent hypersensitivity (de Groat and Yoshimura, 2009;Birder and Andersson, 2013;Yoshimura et al, 2014;Grundy et al, 2018b;Konthapakdee et al, 2019;Grundy et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Bladder afferent nerve activity was determined using an ex vivo model previously described (Daly et al 2007;Grundy et al 2018a). The whole bladder and surrounding tissues (together with its emanating nerve fibres) was placed in a recording chamber (30 ml).…”
Section: Extracellular Afferent Nerve Recordingsmentioning
confidence: 99%
“…Information regarding the state of bladder distension is carried via sensory afferents that project via the pelvic and hypogastric nerves into the dorsal horn of the spinal cord, feeding into autonomic reflex and micturition centres within the brainstem to maintain continence (see Grundy et al 2018a for review). Bladder afferents are found innervating both the detrusor smooth muscle and the urothelium (Spencer et al 2018), consisting of myelinated Aδ fibres and unmyelinated C fibres that exhibit polymodal sensitivity to a host of mechanical and chemical stimuli (Su & Gebhart, 1998;Zagorodnyuk et al 2006Zagorodnyuk et al , 2007.…”
Section: Introductionmentioning
confidence: 99%